Correlation analysis of age and MTHFR C677T polymorphism with sperm motility and sperm DNA integrity: Correlation of age and MTHFR C677T with sperm quality - Xin, Zenglian; Han, Ningning; Jin, Huiya (Cellular and Molecular Biology, 2023)
Several factors, including age and polymorphisms in genes such as MTHFR, affect sperm quality. However, the relationship between MTHFR C677T polymorphism and infertility remains unclear. Hence, the purpose of this study was to investigate the effects of age and methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism on the forward progressive sperm motility and sperm DNA integrity. For this purpose, a total of 845 men were recruited from the hospital's infertility clinic for semen analysis, sperm DNA integrity testing, and MTHFR C677T genotyping. The participants were grouped by age (<30 years, 30-35 years, >35 years) to determine the relationship between age and the progressive motility of sperms (PR%) and sperm DNA integrity. The effect of MTHFR C677T polymorphism on sperm motility and sperm DNA integrity was also analyzed in all the age groups. Results showed that PR% and DNA fragmentation index (DFI) differed significantly among the groups (P<0.001). The correlation analysis showed that age was positively correlated with DFI and negatively correlated with PR%. DFI correlated negatively with PR% (P <0.01). When the age groups were classified based on the C677T genotype, we observed that PR% and DFI did not differ significantly between different genotypes within the same age range (P>0.05). The conclusion was that age exerted a negative effect on sperm motility and sperm DNA integrity. Age correlated positively with DFI and negatively with PR%. MTHFR C677T polymorphism did not affect forward motile sperm count and sperm DNA integrity. Our observations will be useful for fertility guidance and MTHFR genotype interpretation in the clinic for couples of childbearing age.